Impairment of attention network function in posterior circulation ischemia-evidence from the Attention Network Test - Li, Na; Li, Chuanjin; Xie, Xiaohui; Liu, Gang; Wang, Kai; Zhang, Wendong; Fan, Jin (Frontiers in Human Neuroscience, 2023)
Objective: This study aimed to investigate the effect of posterior circulation ischemia (PCI) on the function of the attention networks and to determine whether PCI is a global or selective attention network deficiency and which attention network is affected. Methods: Thirty-six patients with PCI aged 30 to 75 years were evaluated using the attention network test and the Mini-Mental State Examination (MMSE). There were no significant differences between the PCI group and the control group (n=32) in terms of age, sex, education level, and other aspects. All data were statistically analyzed by SPSS 23.0 software. Result: The MMSE scores of the two groups were above 24, and the difference was not significant (P>0.05).The response time for the alerting and orienting network of the PCI group (28.36±15.62 ms and 29.42±14.52 ms, respectively) were significantly shorter than those of the control group (39.41±16.85 ms and 39.44±12.37 ms, respectively), and the differences were significant (P<0.05). The executive control network response time of the PCI group was significantly longer than that of the control group (130.5±41.81 ms vs.100.66±30.3 ms; P<0.05). The overall mean reaction time of the PCI group was also significantly longer than that of normal control group (740.33±76.60 ms vs. 592.25±58.25ms; P<0.05). There was no significant difference in the average accuracy between the two groups. Conclusion: The efficiency of the alerting, orienting, and executive control networks in PCI patients was significantly lower than that in the control group participants (P<0.05). This demonstrates that the functioning of the attention networks are impaired in PCI patients.Since transient nerve seizures caused by vertebrobasilar ischemia may precede posterior circulation stroke, early assessment of cognitive function in patients with PCI is particularly important, and ANT is an excellent tool for this assessment.